2012
DOI: 10.1007/s00213-012-2910-y
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Neuropeptide S receptor blockade decreases discriminative cue-induced reinstatement of cocaine seeking in the rat

Abstract: The identification of the NPS/NPSR system as an important new element involved in the physiopathology of cocaine addiction and the discovery of the anti-addictive properties of NPSR antagonists opens the possibility of exploring a new mechanism for cocaine addiction treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…And interestingly, the response-reinstating effect of menthol was observed only in rats that had been trained to self-administer nicotine with pre-session menthol but not in the rats that had received exactly the same nicotine self-administration training but without pre-session menthol. This finding can be explained in the frame of the above discussed occasion-setting effect of menthol and is consistent with previous studies, in which discriminative stimuli effectively reinstated extinguished drug-seeking behavior in animals that were trained to self-administer cocaine, heroin, alcohol, nicotine, and sucrose (Alvarez-Jaimes et al, 2008; Barker et al, 2014; Burbassi and Cervo, 2008; Ciccocioppo et al, 2001; Gracy et al, 2000; Kallupi et al, 2013; Katner et al, 1999; Widholm et al, 2011; Wing and Shoaib, 2008). The present results mirror our previous report that showed that caffeine influences nicotine seeking (Liu and Jernigan, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…And interestingly, the response-reinstating effect of menthol was observed only in rats that had been trained to self-administer nicotine with pre-session menthol but not in the rats that had received exactly the same nicotine self-administration training but without pre-session menthol. This finding can be explained in the frame of the above discussed occasion-setting effect of menthol and is consistent with previous studies, in which discriminative stimuli effectively reinstated extinguished drug-seeking behavior in animals that were trained to self-administer cocaine, heroin, alcohol, nicotine, and sucrose (Alvarez-Jaimes et al, 2008; Barker et al, 2014; Burbassi and Cervo, 2008; Ciccocioppo et al, 2001; Gracy et al, 2000; Kallupi et al, 2013; Katner et al, 1999; Widholm et al, 2011; Wing and Shoaib, 2008). The present results mirror our previous report that showed that caffeine influences nicotine seeking (Liu and Jernigan, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…This finding agrees with a previous study reporting that RTI-118 also produced a dose-dependent and nearly complete elimination of cocaine self-administration in rats while producing little or no effect on food-maintained responding (Schmoutz et al, 2012). RTI-118 and other NPS receptor antagonists have also been found to block cue-, cocaine-, and stress-induced reinstatement of cocaine self-administration in rats and mice (Kallupi et al, 2010; Kallupi et al, 2013; Paneda et al, 2009; Schmoutz et al, 2012). Taken together, these results support further consideration of NPS receptor antagonists as treatments for cocaine abuse and dependence.…”
Section: Discussionmentioning
confidence: 99%
“…When administered into the LH, NPS enhances reinstatement of alcohol and cocaine seeking triggered by environmental conditioning factors. This effect is blocked by peripheral administration of the OX1 antagonist SB334867, which suggests an important interaction between these two peptidergic systems (15,16,19). In addition, NPS facilitates cocaine reinstatement with mechanisms mimicking, at least in part, the effect of stress and that may involve the corticotropin releasing factor and the Hcrt-1/Ox-A systems as well (20)(21)(22).…”
mentioning
confidence: 86%
“…Guide cannulae for drug injections were stereotaxically aimed at the following regions: LH [we previously demonstrated that NPS stimulates Hcrt-1/Ox-A neurons when microinjected into the perifornical and lateral hypothalamic regions of the rat tuberal hypothalamus (15,19); therefore, in the present work, we used stereotaxic coordinates, allowing us to diffuse NPS into both areas], locus coeruleus (LC), ventral tegmental area (VTA), PVN, and BNST. Cannulae were always implanted bilaterally, except for the injection of the retrotracer in experiment 5 where they were implanted unilaterally in the PVN and BNST.…”
Section: Intracranial Surgerymentioning
confidence: 99%